2015
DOI: 10.3109/13880209.2014.997251
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of physcion 8-O-β-glucopyranoside isolated fromPolygonum cuspidatumon learning and memory in dementia rats induced by Aβ1–40

Abstract: Conclusions: PSG can significantly enhance learning and memory in Ab 1-40 -induced dementia rats, and the mechanisms may be related to increase levels of Ach, 5-HT, NE, and DA, decrease Ab contents, and up-regulation of drebrin proteins in hippocampus. KeywordsAlzheimer's disease, drebrin, Morris water maze test History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The subsequent effects of ACh depend on the role of AChE in the synaptic cleft; AChE can hydrolyze ACh into choline and acetic acid, which has a very high catalytic activity, thus ensuring that the concentration of ACh declines rapidly (21). Therefore, AChE and choline acetyltransferase activities in the brain can indirectly reflect ACh content, and can thus be used to infer the functional status of the central cholinergic system (22). Furthermore, the present study indicated that tetrahydropalmatine significantly decreased the ketamine-induced increase in AChE activity and reversed the ketamine-induced decrease in ACh levels, demonstrating that tetrahydropalmatine protected nerve cell apoptosis in ketamine-induced mice.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent effects of ACh depend on the role of AChE in the synaptic cleft; AChE can hydrolyze ACh into choline and acetic acid, which has a very high catalytic activity, thus ensuring that the concentration of ACh declines rapidly (21). Therefore, AChE and choline acetyltransferase activities in the brain can indirectly reflect ACh content, and can thus be used to infer the functional status of the central cholinergic system (22). Furthermore, the present study indicated that tetrahydropalmatine significantly decreased the ketamine-induced increase in AChE activity and reversed the ketamine-induced decrease in ACh levels, demonstrating that tetrahydropalmatine protected nerve cell apoptosis in ketamine-induced mice.…”
Section: Discussionmentioning
confidence: 99%
“…Asian royal fern --- [39] Frangula rupestris ---Stem bark [21] Vismia rubescens ---Stem bark [33] Eurotium cristatum ------ [41] Reynoutria elliptica Asian knotweed --- [31] Microsporum sp ------ PG is a biologically active component of Rheum palmatum [44], Rheum officinale, Polygonum multiflorum, Polygonum reynoutria [45], Polygonum cuspidatum [46], Reynoutria sachalinensis [47], Fallopia sachalinensis [48] and Rumex japonicus Houtt (Figure 2) [49][50][51][52].…”
Section: Osmunda Japonicamentioning
confidence: 99%
“…The biologically and pharmacologically active anthraquinones, physcion and PG have been wellknown for their potential anti-cancer [19, 22-23, 28, 49, 51] and anti-inflammatory activities [34,53]. Moreover, physcion also shows anti-microbial [33] and hepatoprotective properties [54] while PG displays ameliorative effects against dementia [46] and have anti-sepsis properties [55]. This review spotlights on the mechanism by which both these compounds act to combat cancer progression.…”
Section: Biological Activities Of Physcion and Pgmentioning
confidence: 99%
“…Physcion 8-O-β-glucopyranoside (PSG) isolated from knotweed can significantly enhance learning and memory in Aβ1-40-induced dementia rats, and the mechanisms may be related to increase levels of acetylcholine, serotonin, noradrenaline, and dopamine, decrease Aβ contents, and up-regulation of dendritic spine protein drebrin [99] (Shim et al, 2002) in hippocampus [100].…”
Section: Physcion 8-o-β-glucopyranosidementioning
confidence: 99%